Microwave dielectric characterization of Ca0.6(La1-xYx)0.2667TiO3 perovskite ceramics with high positive temperature coefficient. Issue 12 (15th June 2021) - Lin, Shih-Hung; Lin, Zi-Qi; Chen, Chi-Wei
Abstract: Solid solution Ca0.6 (La1-x Yx )0.2667 TiO3 dielectric ceramic systems with various x values were studied, which were prepared using a solid-state reaction method. X-ray diffraction and X-ray spectroscopy analyses showed that the crystal structure of these samples was orthorhombic perovskite. The microstructures with the substitution amount of Y 3+ and the dielectric performances of the Ca0.6 (La1-x Yx )0.2667 TiO3 ceramics were also explored. With x = 0.1, the Ca0.6 (La0.9 Y0.1 )0.2667 TiO3 ceramic could be sintered at 1350 °C, and the microwave dielectric performance was found to be strongly correlated with the sintering temperature. A maximum Qf value of 23, 100 (GHz), dielectric constant ( ε r ) of 111, and temperature coefficient (τ f ) of 374.6 ppm/°C were achieved for samples sintered at 1350 °C for 4 h. This dielectric ceramic possessed good potential as a τ f compensator to obtain a near-zero τ f mixture for high-quality substrates for use in wireless communication systems.